2018
DOI: 10.1111/ijal.12196
|View full text |Cite|
|
Sign up to set email alerts
|

Syntactic complexity in L2 writing: Individual pathways and emerging group trends

Abstract: The present study aims to contribute to a fuller understanding of how the L2 production of L2 learners varies over time in terms of syntactic complexity by analyzing a substantive number of English L2 writing samples (n = 11) produced by a sizable group of learners (n = 10) over a relatively long period of time (19 months), using a judicious selection of quantitative measures of syntactic complexity. The focus is on synchronic and diachronic variation, both within and across learners. Our analyses show that wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 34 publications
1
38
0
10
Order By: Relevance
“…An explanation for these results is the notion that the process of learning an L2 is nonlinear and incremental, in which small changes occur over time (Murakami, 2016), thereby coinciding with previous research which has found evidence for nonlinearity in L2 development (e.g., Bulté and Housen, 2018;Murakami, 2016). Another conceivable explanation for the observed nonlinearity may be that, as the experiment progressed, learners might have experienced fatigue, boredom or any other non-developmental individual factors (Bulté and Housen, 2018). It is important to note, however, that the results of the reading questionnaire showed that, on average, learners mostly enjoyed reading the experimental texts.…”
Section: Research Question 2: Does the Potential Role Of These Indivisupporting
confidence: 82%
“…An explanation for these results is the notion that the process of learning an L2 is nonlinear and incremental, in which small changes occur over time (Murakami, 2016), thereby coinciding with previous research which has found evidence for nonlinearity in L2 development (e.g., Bulté and Housen, 2018;Murakami, 2016). Another conceivable explanation for the observed nonlinearity may be that, as the experiment progressed, learners might have experienced fatigue, boredom or any other non-developmental individual factors (Bulté and Housen, 2018). It is important to note, however, that the results of the reading questionnaire showed that, on average, learners mostly enjoyed reading the experimental texts.…”
Section: Research Question 2: Does the Potential Role Of These Indivisupporting
confidence: 82%
“…Syntactic and lexical complexity are two important and major components of complexity, which is the most frequently studied construct of CAF (Bulté & Housen, 2012; Kuiken, Vedder, Housen, & De Clercq, 2019). Numerous studies have shown that syntactic complexity and lexical richness indices can serve as pertinent and valid descriptors of writing and speaking task performance (Kyle & Crossley, 2016; Lu, 2011, 2012) and indicators of language proficiency (Bulté & Housen, 2012, 2018). For this reason, syntactic complexity and lexical richness measures are adopted by this study to describe the linguistic performance in the compositions of learners.…”
Section: Literature Reviewmentioning
confidence: 99%
“…I faglitteraturen er der mange syntaktiske kompleksitetsindekser at vaelge mellem, og forskellene mellem de enkelte indekser har baggrund i, hvilke niveauer af syntaktisk analyse de undersøgte/målte strukturer stammer fra og hvilke aspekter af strukturernes kompleksitet der skal måles. For eksempel anvendte Bulté og Housen [Bulté, Housen, 2018] et saet indekser, der daekker såvel saetnings-og t-enhedsniveau som delsaetnings-(clause-) og fraseniveauet. Lu [Lu, 2010] opdelte derimod sit saet af kompleksitetsindekser i fem grupper efter hvilke egenskaber de er designet til at måle.…”
Section: De Anvendte Kompleksitetsindekserunclassified
“…Angående videre forskning synes det hensigtsmaessigt at anvende et større saet kompleksitetsindekser, som vil daekke over flere niveauer af syntaktisk analyse (jf. [Bulté, Housen, 2018]) samt flere diverse aspekter af den syntaktiske kompleksitet (jf. [Lu, 2010]).…”
Section: Konklusionerunclassified
See 1 more Smart Citation